Free-sugar, total-sugar, fibre, and micronutrient intake within elite youth British soccer players: a nutritional transition from schoolboy to fulltime soccer player - Naughton, R. J.; Drust, B.; O`Boyle, A.; Abayomi, J.; Mahon, E.; Morton, J. P.; Davies, I. G. (Applied Physiology, Nutrition, and Metabolism, 2017)
It is recommended that soccer players consume a high carbohydrate diet to augment performance. However, growing evidence suggests that there is a link between high free-sugar (FS) intake (>5% total energy intake; TEI) and metabolic diseases. Furthermore, foods that are often high in sugar, such as processed foods, are typically lacking in nutrient quality. We therefore analysed total-sugar, FS, dietary fibre, and micronutrient intake of players from an English Premier League academy under (U) 18 (n = 13), U15/16 (n = 25), and U13/14 (n = 21) using a 7-day food diary. Data were compared with current United Kingdom (UK) dietary reference value (DRV) for FS via a t test. The U13/14s (10% ± 18%) and U15/16s (11% ± 30%) both consumed higher amounts of FS in comparison with the UK DRV of 5% TEI (P < 0.01); conversely, the U18s did not exceed the DRV (5% ± 13%). Furthermore, FS intake of the U18s was significantly lower than the U13/14s and U15/16s (P < 0.01). Dietary fibre was below the DRV (25 g/day for U13/14 and U15/16s; 30 g/day for U18s) for all squads (19.0 ± 4.7, 19.6 ± 8.3, 17.1 ± 4.2 g/day, respectively), but not different between squads. Additionally, micronutrient reference intakes were generally met. In conclusion, we provide novel data on dietary sugar, fibre, and micronutrient intake within elite youth soccer players. We report an apparent "nutritional transition" from schoolboy to fulltime soccer player, with U18s showing a significantly lower intake of sugar in comparison with younger squads, and a similar intake of FS to the UK DRVs. Practitioners should target improving player education around sugar and fibre consumption.